Self-reported maternal morbidity and associated factors among Brazilian women Morbidade materna auto-referida e fatores associados entre mulheres brasileiras - Joao Paulo Souza (Revista da Associação Médica Brasileira, 2008)
PURPOSE: Demographic health surveys may constitute a valuable source of information on maternal morbidity, particularly in locations where an integrated system of epidemiological surveillance with wide geographic coverage has not yet been developed. METHODS: This study analyzed the database obtained from a national Demographic Health Survey carried out in Brasil in 1996. Data regarding how the survey was conducted, characteristics of the women interviewed who had given birth to live infants in the five preceding years, characteristics of the obstetrical care received and complications reported were evaluated. RESULTS: Responses from a weighted total of 3,635 women were analyzed. Statistically significant differences (p<0.001) were found between geographic domains for most characteristics studied. Deliveries were predominantly hospital-based throughout the whole country. Prevalence of self-reported maternal morbidity ranged from 15.5-22.9% in the various geographic domains analyzed. This geographic factor was found to be associated to differences in the occurrence of complications, generally and specifically, for cases of prolonged labour. CONCLUSION: Differences in morbidity may reflect the intricate relationship between determinants of human development and maternal health conditions. OBJETIVOS: Os estudos demográficos de saúde podem constituir fonte valiosa de informação sobre a morbidade materna, especialmente nos locais onde ainda não foi desenvolvido um sistema de vigilância epidemiológica integrado e de ampla cobertura geográfica. MÉTODOS: Este estudo consiste na análise secundária do banco de dados da última Pesquisa Nacional sobre Demografia e Saúde, realizada no Brasil, em 1996. Foram analisados os dados referentes à operacionalização da pesquisa, as características das mulheres entrevistadas que tiveram gestações resultantes em nascidos vivos nos cinco anos precedentes ao inquérito, as características da assistência obstétrica e das complicações referidas por estas mulheres. RESULTADOS: As respostas de um total ponderado de 3.635 mulheres foram analisadas. Foram observadas diferenças significativas (p<0,001) entre os domínios geográficos para a maior parte das características estudadas. A assistência ao parto foi predominantemente hospitalar em todo o país. A prevalência de morbidade materna referida oscilou entre 15,5% e 22,9% nos diferentes domínios geográficos analisados. Este fator geográfico esteve associado a diferenças de risco para a ocorrência de complicações em geral e, mais especificamente, para a ocorrência de trabalho de parto prolongado. CONCLUSÃO: Estas diferenças em morbidade possivelmente refletem o intrincado relacionamento existente entre as determinantes do desenvolvimento humano e as condições de saúde materna.